SPECIFICS OF ETHNOGRAPHIC TOURISM AND ETHNIC TOURISM IN UZBEKISTAN - Agzamova, Nargiza (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
The article presents different definition of "ethnographic tourism", in greatest detail the features of the organization of this kind of tourism. Social functions are allocated ethnotourism. The characteristics of the main components of animation programs in the ethnographic tourism.